Illiquidity, Stock Return and Corporate Capital Structure: Evidence from Seasoned Equity Offering - YU, Zhao (Institutional Knowledge at Singapore Management University, 2009)
The post-issue underperformance of seasoned equity offering (SEO) is generally explained by asymmetric information and deteriorating operating performance. We complement these traditional explanations with a new parameter, the liquidity, which results from the change of capital structure due to equity offering. The new issuing of equity lowers the debt to asset ratio, lowers the information asymmetry, thus increasing stock liquidity, which is in accordance with the hypotheses presented by Kyle(1985)'s model; Evidence that stocks become more liquid after SEO, thus lower the expected return, resulting to underperformance, combined with the high stock illiquidity before SEO, which coincides the high return, proving that Amihud's (2002) hypothesis about the relation between liquidity and stock is applicable in explaining the stock return puzzle during SEO period.